Wohnst Du noch oder sparst Du schon? Eine vergleichende Untersuchung zur Rolle des Wohneigentums für die Altersvorsorge - Dötsch, Jörg (Estonian Discussions on Economic Policy, 2018)
Europe’s social security systems face enormous challenges. Most of the existing pension systems do not seem to be sustainable. That means that private pension provision is becoming increasingly important. This paper presents some key findings of an international research project concerning the question of how residential property can be used to ensure liquidity in old age by means of so called equity release schemes (ERS). The analysis covered Germany, Hungary, Ireland, Italy, the Netherlands and the UK. The first part explains the design of the research project. The next two sections present comparison of the national backgrounds regarding pension provision, housing markets and markets for ERS. The study clearly illustrates that residential property will obviously become more important with regard to future old-age provision. Nevertheless, even if the member states face similar problems, a one-size-fits-all-solution does not seem to be feasible. The regulatory, social and economic characteristics of the member states seem to be too diverse.